Obesity is associated with greater cognitive function in patients with type 2 diabetes mellitus - Xing, Zhenhua; Long, Chen; Hu, Xinqun; Chai, Xiangping (Frontiers in Endocrinology, 2022)
Background The impact of obesity on cognitive function in patients with type 2 diabetes mellitus (T2DM) remains controversial. This study aimed to evaluate whether obesity, assessed by body mass index (BMI) was associated with cognitive function among T2DM patients and whether the effect of obesity on cognitive function was through brain structure. Methods This was a post-hoc analysis of the Action to Control Cardiovascular Risk in Diabetes–Memory in Diabetes (ACCORD-MIND) study. The cognitive test battery included the Digit Symbol Substitution Test (DSST), Mini-Mental State Exam (MMSE), Rey Auditory Verbal Learning Test (RAVLT), and STROOP test, which were administered at baseline, and at 20, 40, and 80 months. A subgroup (n = 614) of the ACCORD-MIND study underwent MRI scanning at baseline and at 40 and 80 months. The total brain volume (TBV), abnormal white matter volume (AWM), abnormal gray matter volume (AGM), and abnormal basal ganglia volume (ABG) were estimated. The outcomes of this study were cognitive function and brain structure. Results In the adjusted analyses, BMI was positively associated with the MMSE (β:0.08, 95%CI,0.01-0.16, per standard deviation [SD] increase) and RAVLT scores (β:0.09, 95%CI,0.01-0.18). It was also associated with a greater TBV (β:7.48, 95%CI,0.29-14.67). BMI was not associated with the DSST or STROOP scores, and AWM, AGM, ABG. Mediation analysis found that the effect of BMI on MMSE/RAVLT was mediated through TBV. Conclusion Obesity may be associated with greater cognitive function and the effect of BMI on cognitive function may be mediated by TBV among patients with T2DM. Clinical Trial Registration http://www.clinicaltrials.gov, identifier NCT00000620.